Pengaruh Smartphone Terhadap Kualitas Tidur pada Siswa Kelas XI di SMA Negeri 1 Barumun Tengah - Abdul Hamid Lubis; Amvina; Siska Futri Nasution (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Excessive use of smartphones is causing a reduction in sleep quality due to reduced sleep time, not sleeping well, delays in starting sleep and waking up, not feeling refreshed when awakened and can cause nightmares, also the use of gadgets causes the brain to receive stimuli from outside in the form of sound. , light, and vibration from gadgets that keep a person awake at night. Smartphone is an electronic device or instrument that has a practical purpose and function, especially to help human work. a small electronic device that has a special function. The purpose of this study was to determine the effect of smartphone use on the sleep quality of SMA Negeri 1 Barumun students, with the research method carried out by researchers using quantitative research, with a descriptive research design that emphasized quality or the most important thing. The population of this study was class XI high school students. Negeri 1 in Barumun Tengah which amounted to 161 people and the sampling was by using a random sampling technique. The instrument of this research used a questionnaire. Data analysis using Correction test. The results of the analysis of 40 respondents who were examined from the use of smartphones, the majority of the results were influential, namely as many as 29 people (72.5%) and the minority did not affect as many as 11 people (27.5%). The results of the Spearman correlation test obtained a significance level of p value of 0.000 (p < 0.05), meaning that Ho was rejected. Ha was accepted. So it can be concluded that there is a significant relationship between the use of smartphones on sleep quality and the researcher's advice to be able to use smartphones in certain things, namely for learning.